Engineering a Carbonyl Reductase as a Potential Tool for the Synthesis of Chiral α‐Tetralinols. Issue 21 (6th September 2021) - Li, Aipeng; Ting, Wang; Yang, Ke; Zhang, Xuanshuo; Yin, Dongming; Qin, Yong; Zhang, Lianbing
Abstract: Tailoring of enzyme toward α‐tetralones, a class of bulky‐bulky ketones, is still a challenge. In this work, the mutants of carbonyl reductase BaSDR1 with improved catalytic performance toward α‐tetralone 1  a were obtained by adjusting the steric hindrance and hydrophobicity of the residues that affect the approach of α‐tetralone with the catalytic residues. The designed mutants also showed enhanced catalytic performance toward halogenated α‐tetralones 2  a –6  a . Remarkably, the activity of the mutant Q237V/I291F toward 7‐fluoro‐α‐tetralone 5  a was 16.3‐fold higher than the wildtype enzyme with improved stereoselectivity (98.8 % ee). More notably, the mutants Q139S and Q139S/V187S exhibited decreased or reversed stereoselectivity toward α‐tetralone 1  a, 5‐bromo‐α‐tetralone 2  a, 7‐fluoro‐α‐tetralone 5  a and 7‐chloro‐α‐tetralone 6  a, while the relatively high ee values were obtained in the presence of 6‐chloro‐α‐tetralone 3  a and 6‐bromo‐α‐tetralone 4  a as substrates. Further analysis showed the larger size of the substrates was beneficial for the substrates binding to the active cavity with a more specific binding mode, which endows the reaction with higher stereoselectivity. Moreover, the recombinant E. coli expressing the variant Q237V/I291F successfully catalyzed the reduction of a high concentration 7‐fluoro‐α‐tetralone 5  a . These results not only offered a potential tool for chiral α‐tetralols, but also provided guiding information for the enzyme engineering toward bulky‐bulky ketones. Abstract : The activity of carbonyl reductase BaSDR1 toward α‐tetralones, a class of bulky‐bulky ketones, was successfully improved by rational design. The relative larger size of the substrates turned out to be crucial factor connected to the higher enzyme stereoselectivity.